2013
DOI: 10.1038/ejcn.2013.126
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of protected mealtimes in reducing mealtime interruptions and improving mealtime assistance in adult inpatients in an Australian hospital

Abstract: The PMP increased nursing staff availability at mealtimes and feeding assistance, but also increased mealtime interruptions. This may explain the lack of change in patient energy and protein consumption. Strategies promoting adherence with PMP implementation, such as nurse ward champions or nursing staff driving PMP implementation, may be required to maximise the benefits of protected mealtimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(109 citation statements)
references
References 14 publications
3
104
1
1
Order By: Relevance
“…The concept of Protected Mealtimes was considered by Dickinson et al (2008) to be an important tool for changing mealtime practices in which patients could eat with interruptions. This contrasts with the findings by Huxtable and Palmer (2013) that suggested that interruptions by the caregivers were increased by providing Protected Mealtimes. However, our study showed, in line with Ullrich et al (2011), that mealtime interventions inspired by Protected Mealtimes are not only about decreasing interruption during mealtimes, but also about providing ownership of mealtime activity to the caregivers, resulting in an increased priority of mealtime care.…”
Section: Comprehensive Understanding and Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The concept of Protected Mealtimes was considered by Dickinson et al (2008) to be an important tool for changing mealtime practices in which patients could eat with interruptions. This contrasts with the findings by Huxtable and Palmer (2013) that suggested that interruptions by the caregivers were increased by providing Protected Mealtimes. However, our study showed, in line with Ullrich et al (2011), that mealtime interventions inspired by Protected Mealtimes are not only about decreasing interruption during mealtimes, but also about providing ownership of mealtime activity to the caregivers, resulting in an increased priority of mealtime care.…”
Section: Comprehensive Understanding and Discussioncontrasting
confidence: 96%
“…However, conflicting results exist regarding the effect of PM on patients. Some studies have suggested that even though patients valued the protected mealtimes, their food intake did not increase (Hickson, Connolly, & Whelan, 2011; Young et al, 2016) and energy and protein consumption did not change (Huxtable & Palmer, 2013). However, the implementation of PM is justified in the research literature by claiming that some aspects of the PM concept showed significant improvement, for example increased mealtime assistance (Porter, Ottrey, & Huggins, 2017), as well as increased mealtime interruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Publication date ranged from 2002 to 2015, with eight published within the last 5 years [32,[39][40][41][42][43][44][45]. The setting in thirteen articles was an acute hospital [32,[39][40][41][42][43][44][45][46][47][48][49][50], with the remaining study set in a short stay dementia assessment unit [51]. The UK was the most common location (7 articles) [39,41,[44][45][46][47]50], followed by Australia (4 articles) [32,42,43,49], the United States (2 articles) [40,48] and New Zealand (1 article) [51].…”
Section: Overview Of Articlesmentioning
confidence: 99%
“…Publication date ranged from 2002 to 2015, with eight published within the last 5 years [32,[39][40][41][42][43][44][45]. The setting in thirteen articles was an acute hospital [32,[39][40][41][42][43][44][45][46][47][48][49][50], with the remaining study set in a short stay dementia assessment unit [51].…”
Section: Overview Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation